Toward An Islamic Alternative In Thought and Knowledge (American Journal of Islam and Society, 1989)
IntroductionCurrent developments and the many acute problems facing the MuslimUmmah, especially at the intellectual level, present a serious challenge toIslam. This is why an attempt to outline an intellectual Islamic alternativein thought and knowledge has never been so urgent and imperative. Thiwill, insha 'Allah, help in formulating a clear and coordinated policy withregard to cultural transformation based on firm principles and sound strategy.It is also hoped that this policy will lead to scientific findings.By way of introduction, I will give a brief description of the state ofknowledge and thought. and of the educational and cultural systems in thecontemporary Arab and Muslim world.The Present State of ThoughtWhen examining the present state of thought among the Muslim peoples.three basic approaches can be identified:• The first can be described as the traditionalist approach which,by and large, considers the "traditional'' thought of the Ummahto be self-sufficient and capable of being presented asit is or with very little alteration. This approach suggeststhat the Ummah's contemporary intellectual life can be formedand organized and that the structure of its civilization canbe built on this basis. This approach i often described asthe approach of authenticity.• The second approach considers contemporary Western thoughtand its world-view-its concepts of existence, of life and ofman-to be universal, without it a modern culture and civilizationcannot be built. This tendency maintains that Westernthought must be adopted in toto, and any consequent negativeaspects are the price that must be paid if a modern cultureand civilization are to be established. This view is oftendescribed as mcdemistic.• The third trend, or the eclectic approach, advocates yetanother view. It contends that one must select from traditionalthought what is most sound, and from "modern" contemporarythought that which one considers and proves tobe correct, and weld the two to form an intellectual structurethat will provide a guaranteed basis for achieving what isrequired.However, the traditional approach, in the manner it has been presentedand applied, did not help to prevent the Ummah from falling into Lhe stateof decline and failure from which it is still suffering. Likewise, Western thought,as it also is presented and applied, cannot protect the Ummah from its inherentadverse, harmful and even disastrous effects. The advocates of theeclectic selective approach have not yet presented the details of this proposedblend, let alone tried to put it into effect. All this is conducive to the widerangingquestion: Is the Umrnah going through a serious intellectual crisis;and . if so, what is the way out of it? ...